2013
DOI: 10.3906/bot-1205-18
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and genetic variation within and among four Quercus petraea and Q. robur natural populations

Abstract: the regions of high diversity for Quercus species (Yaltırık, 1984), which have a natural distribution of about 6.4 million ha (OGM, 2006) including many subspecies, varieties, and natural hybrids.Pedunculate (Quercus robur L.) and sessile [Quercus petraea (Matt.) Liebl.] oaks are 2 sympatric, widespread species with high economic and ecological importance that cover most of Europe from Spain to Russia and Scotland to Turkey (Bodenes et al., 1997). Both species are supposed to exhibit different ecological requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 42 publications
2
19
1
Order By: Relevance
“…In Turkey, both Q. robur and Q. petraea occur in similar semi-humid to arid climates (Ugurlu et al, 2012), suggesting different local adaptations of these species in Turkey compared to the European species distribution range. Based on the precipitation effectiveness index (Erinç, 1965), Yücedağ & Gailing (2013) reported that Q. petraea populations were located in semi-humid conditions and Q. robur populations in semi-arid to arid climates. Likewise, Eaton et al (2016) pointed out that these oak species show phenotypic differences in conditions far from their optimum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Turkey, both Q. robur and Q. petraea occur in similar semi-humid to arid climates (Ugurlu et al, 2012), suggesting different local adaptations of these species in Turkey compared to the European species distribution range. Based on the precipitation effectiveness index (Erinç, 1965), Yücedağ & Gailing (2013) reported that Q. petraea populations were located in semi-humid conditions and Q. robur populations in semi-arid to arid climates. Likewise, Eaton et al (2016) pointed out that these oak species show phenotypic differences in conditions far from their optimum.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, no studies have been performed on the variation of stomatal density and associations with leaf morphological characters in natural populations of Q. petraea and Q. robur in Turkey. The goals of the present study are (1) to assess differences in stomatal densities between species and between populations within species for two populations of Q. robur and two populations of Q. petraea in northwestern Turkey, (2) to analyze associations of stomatal density with seven leaf morphological characters obtained from a previous study (Yücedağ & Gailing, 2013), and (3) to calculate Phenotypic Trait Differentiation (P ST ) between species and between populations within species for stomatal density and seven leaf morphological characters.…”
Section: Introductionmentioning
confidence: 99%
“…Even leaf morphological traits that are frequently used for species identifi cation show a large variability within species and overlapping frequency distributions among species making the distinction of closely related species at single characters diffi cult. However, multivariate analyses using a set of morphometric, numeric and observed leaf characters in sympatric populations can often be used to differentiate between closely related species with some overlap in the phenotypic extremes (Jensen et al 1993, Curtu et al 2007a, Viscosi et al 2012, Yucedag & Gailing 2013. Putative hybrids have been described based on morphological characters (Jensen et al 1993, Rushton 1993 and/or genetic assignment analyses using discriminating genetic markers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…E-Mail: celine.blanc-jolivet@thuenen.de many studies, but with some asymmetry due to stronger interspecific sexual barriers in Q. petraea (CHYBICKI and BURCZYK, 2013;CURTU et al, 2007a;GERBER et al, 2014;LAGACHE et al, , 2014LEPAIS and GERBER, 2011), although signals of past asymmetric introgression toward Q. petraea could be observed at loci with high interspecific differentiation (GUI-CHOUX et al, 2013). Furthermore, both species seem to actively diverge from each other (GOICOECHEA et al, 2012), which probably results in successful morphological and genetic identification of pure and hybrid individuals (CHYBICKI et al, 2010;CURTU et al, 2007a, b;FORTINI et al, 2015;GUGERLI et al, 2007;GUI-CHOUX et al, 2011NEOPHYTOU, 2014;NEOPHYTOU et al, 2015;YÜCEDAG and GAILING, 2013).…”
Section: Introductionmentioning
confidence: 99%